2019
DOI: 10.1039/c9en00557a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the stability of nanoplastics in aqueous environments: effect of ionic strength, temperature, dissolved organic matter, clay, and heavy metals

Abstract: Impact of environmental factors such as temperature, dissolved organic matter, ionic strength and clay colloids on the stability of nanoplastics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
111
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(124 citation statements)
references
References 55 publications
5
111
0
1
Order By: Relevance
“…Stability of plain PS NPs in NSW has been reported in the first hours after the preparation of the suspensions (Mishra et al, 2019), though time-dependent agglomeration that occurred later at 24 and 48 h (Brandts et al, 2018;Tallec et al, 2018;Mishra et al, 2019). From DLS data, Brandts et al (2018) also suggested the sorption capacity of carbamazepine, one of the most common pharmaceuticals found in the environment, onto PS NPs, while NP interaction with heavy metals mostly depends on their speciation in the aquatic environments (Singh et al, 2019). Differently from plain and PS-COOH NPs, once suspended in NSW, positively charged PS NPs usually display a hydrodynamic size close to their nominal diameter (Wu et al, 2019).…”
Section: Ps Np Behavior In Seawater Mediamentioning
confidence: 98%
See 4 more Smart Citations
“…Stability of plain PS NPs in NSW has been reported in the first hours after the preparation of the suspensions (Mishra et al, 2019), though time-dependent agglomeration that occurred later at 24 and 48 h (Brandts et al, 2018;Tallec et al, 2018;Mishra et al, 2019). From DLS data, Brandts et al (2018) also suggested the sorption capacity of carbamazepine, one of the most common pharmaceuticals found in the environment, onto PS NPs, while NP interaction with heavy metals mostly depends on their speciation in the aquatic environments (Singh et al, 2019). Differently from plain and PS-COOH NPs, once suspended in NSW, positively charged PS NPs usually display a hydrodynamic size close to their nominal diameter (Wu et al, 2019).…”
Section: Ps Np Behavior In Seawater Mediamentioning
confidence: 98%
“…Negatively charged PS NPs, such as PS-COOH NPs, are usually prone to agglomerate in the range of 0.9-1.8 µm soon after dispersion in aqueous media characterized by high ionic strength (>38 ), basic pH, and NOM. Such agglomeration phenomena are largely supported by the DLVO theory and related extensions (Cai et al, 2018;Singh et al, 2019;Wu et al, 2019). Examples are represented by microalgae culture medium (Bergami et al, 2017) and NSW (Della Torre et al, 2014;Bergami et al, 2016;Manfra et al, 2017;Tallec et al, 2018;Grassi et al, 2019), where slight differences in NP agglomerates and size distribution are potentially related to the spatial and temporal variability in seawater chemical composition (i.e., organic matter and ions).…”
Section: Ps Np Behavior In Seawater Mediamentioning
confidence: 98%
See 3 more Smart Citations